2016
DOI: 10.1016/j.canlet.2016.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming metabolism by histone methyltransferase NSD2 drives endocrine resistance via coordinated activation of pentose phosphate pathway enzymes

Abstract: A B S T R A C TMetabolic reprogramming such as the aerobic glycolysis or Warburg effect is well recognized as a common feature of tumorigenesis. However, molecular mechanisms underlying metabolic alterations for tumor therapeutic resistance are poorly understood. Through gene expression profiling analysis we found that histone H3K36 methyltransferase NSD2/MMSET/WHSC1 expression was highly elevated in tamoxifenresistant breast cancer cell lines and clinical tumors. IHC analysis indicated that NSD2 protein overe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 44 publications
(71 reference statements)
1
58
0
Order By: Relevance
“…Resistance to endocrine therapies is a major issue in recurrent ER+ HBC patients (De Marchi et al ., 2016). Several mechanisms have been connected to endocrine resistance, such as mutation in the ligand‐binding domain of the ER (Toy et al ., 2013), enhanced growth factor signaling, altered DNA methylation of specific genes (Graff et al ., 1995; Widschwendter and Jones, 2002), or the dysregulation of metabolic pathways (Wang et al ., 2016). In our study, we discovered a novel mechanism demonstrating that Tam decreases Brf1 expression and Pol III gene transcription (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to endocrine therapies is a major issue in recurrent ER+ HBC patients (De Marchi et al ., 2016). Several mechanisms have been connected to endocrine resistance, such as mutation in the ligand‐binding domain of the ER (Toy et al ., 2013), enhanced growth factor signaling, altered DNA methylation of specific genes (Graff et al ., 1995; Widschwendter and Jones, 2002), or the dysregulation of metabolic pathways (Wang et al ., 2016). In our study, we discovered a novel mechanism demonstrating that Tam decreases Brf1 expression and Pol III gene transcription (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that NSD2 is up-regulated in multiple types of human cancers, including small-cell lung cancers, stomach cancer, neuroblastoma, colon cancer, hepatocellular carcinoma, ovarian carcinoma and prostate cancer (16)(17)(18)(19)(20)(21)(22). Furthermore, NSD2 has been demonstrated to support the proliferation and/or survival of many cancer cell lines, such as prostate cancer (22)(23)(24), myeloma cell lines with t (4;14) translocations (25)(26)(27)(28) and leukemia cell lines carrying the E1099K mutation (29), Wang et al (30) has found that NSD2 regulates glucose metabolism; however, whether NSD2 plays roles in diabetes has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…While there is limited evidence of NSD1 dysregulation in breast cancer (Vougiouklakis et al., 2015), NSD2/MMSET overexpression is associated with tumor aggressiveness (Kassambara et al., 2009). Moreover, NSD2 may play a role in drug resistance, since tamoxifen‐resistant breast cancer cell lines have highly elevated NSD2, and only wild type NSD2, but not its methylase‐defective mutant conferred resistance to tamoxifen (Wang et al., 2016). Consistent with this, NSD2 overexpression is highly correlated with poor survival in tamoxifen‐treated patients (Wang et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, NSD2 may play a role in drug resistance, since tamoxifen‐resistant breast cancer cell lines have highly elevated NSD2, and only wild type NSD2, but not its methylase‐defective mutant conferred resistance to tamoxifen (Wang et al., 2016). Consistent with this, NSD2 overexpression is highly correlated with poor survival in tamoxifen‐treated patients (Wang et al., 2016). Notably, NSD2/MMSET and the H3K27 methyltransferase EZH2 (discussed below) are co‐expressed at high levels in cancers including breast and prostate in which EZH2's oncogenic activity was reported to require NSD2/MMSET (Asangani et al., 2013).…”
Section: Introductionmentioning
confidence: 99%